As reclamações registradas contra as escolas e os profissionais da educação na Rede Municipal de Ensino de São Paulo - Pereira, Elaine Aparecida (2020)
This research aimed to analyze the formally registered complaints against the school and the education professionals of the São Paulo Municipal Chain of Education (RME-SP). The study was oriented based on the following questions: 1) What are the formally registered complaints against the school and education professionals in a Regional Offices of Education (DRE) of the RME-SP?; 2) What do the formally registered complaints against the school and the education professionals reveal about the care provided at the school, the performance of its professionals and the relations between the members of the school community? and 3) What are the complainants' expectations regarding school work? In order to answer these questions, the documentary analysis of 1608 records containing the formal complaints against the school and the education professionals, registered in the supervisory duty of one of the 13 DRE was used as an investigation procedure, between 2005 to 2010 and 2015 to 2016. The general hypothesis was formulated in the following terms: regardless of the complainants' level of awareness, the complaints express exactly the ambiguity between the pursuit of democratization of social relations in school and the ideological control of school practices. The study took as theoretical reference the formulations of authors of the critical theory of society, Adorno, Horkheimer, Marcuse, Rusche, Kirchheimer and Neumann, about technological rationality, the managed society and the Law as an instrument of regulation of social relations and, therefore, of control. The research results show that, among other aspects, the majority of complaints filed against the school and its professionals refers to issues related to school administration, followed by complaints regarding personal relationships between school community members whereby only a minority of the records contain complaints pertaining to pedagogical issues